Retraction Note to "Quality Evaluation of Breakfast Cereal Meal Produced from Finger Millet (Eleusine coracana) and Roasted African Yam Beans (Sphenostylis stenocarpa) Flour Blends" [Food Science and Engineering, Volume 4 Issue 2 (2023), 182-190] - Universal Wiser Publisher (Food Science and Engineering, 2026)
This article has been retracted at the request of the Editor. Owheruo JO, Edo GI, Bashir ZA, Akpoghelie PO, Agbo JJ. Quality Evaluation of Breakfast Cereal Meal Produced from Finger Millet (Eleusine coracana) and Roasted African Yam Beans (Sphenostylis stenocarpa) Flour Blends. Food Science and Engineering. 2023; 4(2): 182-190. Following publication, a post-publication review conducted by the journal identified that multiple references cited in the article are not relevant to the subject matter of the study. This indicates insufficient engagement with the established and relevant scholarly literature and does not meet the journal’s standards for academic rigor and citation practice. In light of these findings, the Editor has lost confidence in the reliability of the article’s scholarly foundation, as well as in the validity of its results and conclusions, and has therefore decided that retraction of the article is warranted. This retraction is issued in accordance with the guidelines of the Committee on Publication Ethics (COPE) to ensure the integrity and accuracy of the scholarly record. The editorial office remains committed to maintaining high standards of academic quality and will continue to strengthen its editorial and peer-review processes to ensure that all published manuscripts comply with established publishing standards and accepted principles of research integrity. The editorial office apologizes to readers for any inconvenience caused by this retraction.